2019
DOI: 10.1111/rec.12931
|View full text |Cite
|
Sign up to set email alerts
|

Sourcing native plants to support ecosystem function in different planting contexts

Abstract: Current guidance on sourcing native plants to support ecosystem function focuses on the high risk of failure when unsuitable material is used in ecological restoration. However, there is growing recognition that risks may be lower and rewards higher at highly disturbed sites isolated from remnant populations, especially when considering support for pollinators, wildlife, and other ecosystem functions. We developed the first decision support tool using expert opinion to assess suitability of different native pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 24 publications
(31 reference statements)
0
6
0
3
Order By: Relevance
“…In both cases, genetic diversity may be reduced compared to natural populations (e.g., Williams & Davis, 1996, but see Reynolds et al, 2012). In the case of commercial seed companies, little may be known about the origins or diversity of commercial populations (Kramer et al, 2019), but if the initial seed source was a small sampling of individuals (especially if from a small or inbred remnant population or other restored populations that may have experienced demographic bottlenecks during establishment), then genetic diversity may be substantially reduced compared to large natural populations. Many commercial seed sources are admixed populations resulting from initial collections from many natural populations within a region, which may help alleviate this potential Figure 1.…”
Section: The Importance Of Rapid Adaptation In Restorationmentioning
confidence: 99%
“…In both cases, genetic diversity may be reduced compared to natural populations (e.g., Williams & Davis, 1996, but see Reynolds et al, 2012). In the case of commercial seed companies, little may be known about the origins or diversity of commercial populations (Kramer et al, 2019), but if the initial seed source was a small sampling of individuals (especially if from a small or inbred remnant population or other restored populations that may have experienced demographic bottlenecks during establishment), then genetic diversity may be substantially reduced compared to large natural populations. Many commercial seed sources are admixed populations resulting from initial collections from many natural populations within a region, which may help alleviate this potential Figure 1.…”
Section: The Importance Of Rapid Adaptation In Restorationmentioning
confidence: 99%
“…However, it has been shown that cultivar plantings may fail to restore ecosystem function (reviewed in Kettenring et al, 2014 ; Lesica & Allendorf, 1999 ; White, 2016 ). For example, a recent meta‐analysis showed that almost 25% of studied non‐local cultivars differed for phenotypic traits, such as flower color, which may decrease their pollinator attraction or suitability (Kramer et al, 2019 ). Another study showed that native bees visited native plants more often than their “nativar” (native cultivar; White, 2016 ), which could undermine the long‐term stability of the restored population.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is possible that some outbreeding depression might occur as a result of these new combinations [47,48]. Therefore we need to take these results with caution, as the context (early estimation under the climate change scenario, non-significant variation among provenances in survival) can hinder some of the advantages of these methods as proposed by different authors [7][8][9][10][11]. These methods can also have some risks in the conservation of the genetic resources of the species in the long term [49], and therefore we will need to show clear advantages over traditional methods to implement them at an operational scale in conditions like the ones tested in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Selecting the most productive seed source for a given area has been a traditional approach by forest managers. At present, information on genetic variability and the predictions provided by climate change science enable different seed sourcing strategies to maximize the future adaptation and resilience of our forests [7][8][9][10][11]. Among the possible strategies, local, predicted, composite, admixture, and climate-adjusted seed sourcing have been widely promoted (see Materials and Methods for a detailed description).…”
Section: Introductionmentioning
confidence: 99%